2001
DOI: 10.1126/science.1059542
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of the Biological Clock in Cultured Fibroblasts

Abstract: In mammals, the central circadian pacemaker resides in the hypothalamic suprachiasmatic nucleus (SCN), but circadian oscillators also exist in peripheral tissues. Here, using wild-type and cryptochrome (mCry)-deficient cell lines derived from mCry mutant mice, we show that the peripheral oscillator in cultured fibroblasts is identical to the oscillator in the SCN in (i) temporal expression profiles of all known clock genes, (ii) the phase of the various mRNA rhythms (i.e., antiphase oscillation of Bmal1 and mP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
299
1
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 432 publications
(336 citation statements)
references
References 20 publications
20
299
1
9
Order By: Relevance
“…[62][63][64] Several studies have shown that the circadian oscillators in fibroblasts are similar to those operative in the SCN, and fibroblasts may serve as a valid in vitro model for molecular oscillators in the brain. 64,[70][71][72] The periods for the circadian gene expression in fibroblasts have been found to correspond well with human circadian physiology and mouse behavior. 71 Although the luminescence reporter assay has the advantage of higher throughput and being less laborious, it is not readily applicable to accurately measure amplitude and overall level of the expression of more than one gene.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…[62][63][64] Several studies have shown that the circadian oscillators in fibroblasts are similar to those operative in the SCN, and fibroblasts may serve as a valid in vitro model for molecular oscillators in the brain. 64,[70][71][72] The periods for the circadian gene expression in fibroblasts have been found to correspond well with human circadian physiology and mouse behavior. 71 Although the luminescence reporter assay has the advantage of higher throughput and being less laborious, it is not readily applicable to accurately measure amplitude and overall level of the expression of more than one gene.…”
Section: Introductionmentioning
confidence: 81%
“…It has been reported that similar components of the clock machinery underlie rhythmic gene expression in cultured fibroblasts as in the central clock in the SCN. 64,70,72 Based on this finding, we investigated properties of circadian oscillators in fibroblast cell lines from patients with bipolar disorder. We found that core genes of the circadian clockwork-BMAL1, PER1, PER2, REV-ERBa, DEC2 and DBP-show similar rhythmic expression pattern in fibroblasts from bipolar patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide useful applications for central mammalian pacemaker research, cell line models must exhibit persistent self-sustained oscillations in circadian gene products, restore animal circadian rhythms in SCN-lesioned hosts and exhibit time-dependent responses to stimuli through regulatory pathways that characterize SCN function. Rhythmic gene expression has been demonstrated in NIH/ 3T3 fibroblasts, Rat-1 fibroblasts and spontaneously immortalized embryonic mouse fibroblasts after synchronizing signals (1)(2)(3)(4)(5). However, there is no published evidence that these lines express spontaneous, self-sustained rhythms or rescue rhythms in SCNlesioned animals (5,6).…”
mentioning
confidence: 99%